Analisis Stilistika Lirik Lagu “Asmalibrasi” Karya Soegi Bornean - Ayo Suwaryo (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
This article contains a stylistic analysis of the lyrics of the song “Asmalibrasi” by Soegi Bornean. The discussion of this article focuses on the aspects of connotative diction and the use of figure of speech in the lyrics. The research method used to analyze the lyrics of the song is a qualitative descriptive method. The data analysis techniques used in this study are (1) selecting data; (2) code; (3) classifying data; (4) data description; and (5) data interpretation. The object of this research is the lyrics of the song